Bioremediation of storage tank bottom sludge by using a two-stage composting system: Effect of mixing ratio and nutrients addition. (July 2017) - Koolivand, Ali; Rajaei, Mohammad Sadegh; Ghanadzadeh, Mohammad Javad; Saeedi, Reza; Abtahi, Hamid; Godini, Kazem
Highlights: A two-stage composting system was effective in oily sludge bioremediation. Approximately 95% of TPH was removed through the two-stage composting system. Addition of adequate amount of nutrients and amendment enhanced removal rate of TPH. TPH degradation correlated with temperature increase and organic carbon consumption. TPH biodegradation fitted to the first- and second-order kinetics. Abstract: The effect of mixing ratio and nutrients addition on the efficiency of a two-stage composting system in removal of total petroleum hydrocarbons (TPH) from storage tank bottom sludge (STBS) was investigated. The system consisted of ten windrow piles as primary composting (PC) followed by four in-vessel reactors as secondary composting (SC). Various initial C/N/P and mixing ratios of STBS to immature compost (IC) were examined in the PC and SC for 12 and 6 weeks, respectively. The removal rates of TPH in the two-stage system (93.72–95.24%) were higher than those in the single-stage one. Depending on the experiments, TPH biodegradation fitted to the first- and second-order kinetics with the rate constants of 0.051–0.334 d −1 and 0.002–0.165 g kg −1  d −1, respectively. The bacteria identified were Pseudomonas sp., Bacillus sp., Klebsiella sp., Staphylococcus sp., and Proteus sp. The study verified that a two-stage composting system is effective in treating the STBS.